Enhanced magnetic performance of lead-free (Bi0.5Na0.5)TiO3-CoFe2O4 magnetoelectric ceramics - Parkpoom Jarupoom (2018)
© 2015, The Korean Institute of Metals and Materials and Springer Science+Business Media Dordrecht. This research was conducted to study the magnetoelectric ceramics with the composition belonging to (1-x)(Bi < inf > 0.5 < /inf > Na < inf > 0.5 < /inf > )TiO < inf > 3 < /inf > -xCoFe < inf > 2 < /inf > O < inf > 4 < /inf > or (1-x)BNT-xCF (when x = 0 - 0.02 mol fraction). All compositions have been synthesized by a conventional mixed oxide method and sintered at the temperature ranging of 900°C–1150°C. The ceramics were fabricated to investigate the effects of CF on crystal structure, microstructure, magnetoelectric effect (ME) and electrical properties of BNT ceramic. The optimum sintering temperature was found to be 1100°C for pure BNT ceramic and 1000°C for BNT-CF sample group. X-ray diffraction pattern revealed that all compositions exhibited a single perovskite structure without impurity phase. Diffraction peaks from the amount of CF were not observed in these patterns which may be due to the relatively low concentration of CF added into BNT ceramic and may be below the detection limit of the instrument. The reduction of grain size and dielectric improvement were observed when CF was added. The addition of CF improved the magnetic behavior as well as resulted in a slight change in ferroelectric properties. The addition of 2 mol. % CF into BNT was found to be the optimal composition for produce the magnetoelectric materials simultaneously exhibiting good ferromagnetic and ferroelectric properties at room temperature. [Figure not available: see fulltext.]